Training of Creating Kamishibai as Disaster Mitigation Education Media for Science Teachers - Indarini Dwi Pursitasari; Dadang Jaenudin; Muhammad Iqbal Suriansyah; Indriyani Rachman; Fumithosi Murae; Embun Khoerunnisa Maya Safitri (Yayasan Keluarga Guru Mandiri, 2025)
Sukabumi is one of the areas prone to disasters. However, awareness of disasters among teachers and students is still low. Key issues at MGMP IPA Sukabumi include the need for innovative learning, the competency development of science teachers, interactive learning processes, and a comprehensive disaster mitigation curriculum. Training was conducted to overcome the last problem of developing disaster mitigation learning media. Activities include sending students to the Sakura Exchange Program, pre- and post-questionnaire administration on disaster awareness and risk reduction, mapping, and making Kamishibai at SMPN 1 Cikakak. Data collection using closed and open questionnaires to explore disaster awareness and risk reduction. The collected data were processed descriptively, qualitatively, and quantitatively. This training has succeeded in increasing disaster awareness among teachers and the community. This activity recommends ongoing disaster training and socialization to improve mitigation efforts. A contribution to the world of science education is to integrate disaster mitigation into the curriculum, increase the capacity of teachers as agents of change, strengthen community-based disaster mitigation education, and support the achievement of the SDGs.